Millions of Election Outcomes from a Single Profile - Donald G. Saari (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1991)
By changing the choice of a positional voting method, different election rankings can results from a fixed profile. A geometric theory is developed to explain why this occurs, to completely characterize all possible sets of rankings that can arise in this manner, to determine the number of rankings and other properties of these sets of rankings, to design profiles that cause the different conclusions, to develop elementary tools to analyze actual data, and to compare new types of social choice solutions that are based on the set of rankings admitted by a profile. A secondary theme is to indicate how results for voting theory can be obtained with (relative) ease when they are analyzed with a geometric approach.
Keywords: 330